2018
DOI: 10.21608/ajas.2018.14899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation, Foliar Spray with Nano-fertilizer (Lithovit) and N-levels on Productivity and Quality of Durum Wheat under Toshka Conditions

Abstract: Tow field experiments were carried out at the Experimental Farm of the Water Studies and Research Complex (WSRC) Station, National Water Research Center, in Abu Simbel, Toshka Region, Egypt during two winter seasons 2015-16 and 2016-17. The main objectives were to study the effect of different irrigation levels [A 1 =100% of crop water requirements (ET crop), A 2 =80% ET C and A 3 =60% ET C ], three rates of nano-fertilizer (lithovit) (B 1 =0, B 2 = 200 and B 3 =400ppm), three levels of nitrogen fertilizer (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
6
9
0
Order By: Relevance
“…These results indicate that the studied genotypes responded differently when they were grown at different levels of nitrogen. These results are in agreement with Abdel Nour et al (2011), Abd El-Raouf et al 2013, Ati et al (2016), and Morsy et al (2018). Hindi et al (1990) found low significantly of variety x season x nitrogen interaction for traits related to lodging resistance traits.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These results indicate that the studied genotypes responded differently when they were grown at different levels of nitrogen. These results are in agreement with Abdel Nour et al (2011), Abd El-Raouf et al 2013, Ati et al (2016), and Morsy et al (2018). Hindi et al (1990) found low significantly of variety x season x nitrogen interaction for traits related to lodging resistance traits.…”
Section: Resultssupporting
confidence: 88%
“…Yasser and Naheif (2018) noted that the variation of yield and its attributes in response to increasing N fertilization levels in wheat varieties, to the genetic constitution ability of the genotypes to benefit from the amount of N applied. These results are in agreement with those mentioned by Atia et al (2016), Jarecki et al (2017), Solomon and Anjulo (2017) and Morsy et al (2018). Moreover, some genotypes gave highly significantly grain yield/m 2 .…”
Section: Grain Yield/msupporting
confidence: 93%
“…The reduction of plant height could be attributed to the reduction in cell turgor, along with the inhibition of cell division and expansion. (Abdelkhalek et al, 2015;Abdrabbo et al, 2016;Teama et al, 2016;Attia et al, 2018;Morsy et al, 2018). The reduction in chlorophyll content under water stress could be due to the inhibition of photosynthesis process as a result of the acceleration in chlorophyll degradation (Wu et al 2008;Hafez and Gharib, 2016).…”
Section: Plant Growth Yield and Yield Characteristicsmentioning
confidence: 99%
“…Plant height, leaf chlorophyll, fresh and dry weights of plants increased by lithovit treatments (Ghatas & Mohamed, 2018). The micronutrients supplied with lithovit such as Mn, Cu, Z, among others, influence plant physiology and metabolism and cell wall formation (Morsy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%